2001
DOI: 10.1149/1.1413702
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Mechanical Planarization of Copper and Barrier Layers by Manganese(IV) Oxide Slurry

Abstract: Deep dishing and erosion are serious problems in conventional chemical mechanical planarization ͑CMP͒ of copper/barrier layer, specifically when a hard barrier layer is used as the polishing stopper. This paper describes the reduction of the dishing in the CMP with lower removal rate ratio. This CMP can be achieved by following procedures. ͑i͒ Increase of removal rate in barrier layer; removal rate is 1.5 nm/min in polycrystalline tantalum nitride barrier layer. This rate increases to 77 nm/min in TaSiN barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] However, various defects, such as Cu dishing and oxide erosion, can occur during the CMP process. Cu dishing depth ͑DD͒ is affected by many process parameters, including the Young's modulus of the polishing pad.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] However, various defects, such as Cu dishing and oxide erosion, can occur during the CMP process. Cu dishing depth ͑DD͒ is affected by many process parameters, including the Young's modulus of the polishing pad.…”
mentioning
confidence: 99%
“…When 1 wt% MnO 2 was added to 10 wt% silica, the RRs of SiC were still relatively high at ∼1200 nm h −1 . Since MnO 2 by itself is a good abrasive, oxidizer and was used to polish Cu, SiO 2 , low-K dielectrics films and different types of crystalline SiC films, 22,24,[28][29][30][31] we polished a-SiC wafers with 1 wt% MnO 2 powder alone and found that the RRs were only ∼260 nm h −1 , perhaps due to the reduced abrasive action. These data suggest the possibility of strong interaction between the copper and manganese based additives and the a-SiC surface but also emphasize the need for abrasive action to obtain high RRs.…”
Section: Resultsmentioning
confidence: 99%
“…Scratch-free polishing is possible by this chemical polishing for the copper conductive layer, as reported elsewhere. 11 The critical pressure, P c , is defined as the pressure at which peeling occurs during polishing, where polishing pressure increased gradually with 50 g/cm 2 step. This pressure was determined practically in the chemical polishing for copper layers deposited on type A and B seed layers.…”
Section: Resultsmentioning
confidence: 99%